Percepción, Valoración y Expresión De Las Emociones Básicas En Niños y Niñas De Jardín y Transición. (2014)
The objective of this research is to analyze the capacity of perception, assessment and expression of basic emotions in boys and girls, in the preschool stage, based on Mayer & Salovey's model of emotional intelligence (1997), who consider that although it is not possible to evaluate emotional intelligence at early age, if it can be done from their ability to perceive and value the emotional expressions. The theoretical framework addresses the Emotional Intelligence model from which the investigative interest is supported, definitions of Intelligence Emotional, emotions in general, basic emotions in children and the stage preschool, in their social, cognitive and emotional development. The research is quantitative descriptive type, with a sample of 60 children, aged between 4 and 6 years; of grades garden 3, 4 and transition 3, 4 with groups each of 30 students. The instrument applied is the PERVALEX in its version 2.0 developed by Mestre and Guil R. (2011).